2013
DOI: 10.1063/1.4794313
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states, conical intersections, and spin-rovibronic spectroscopy of the nitrogen oxide sulfide radical

Abstract: Highly correlated ab initio methods are used to investigate the lowest electronic states of doublet and quartet spin multiplicities for SNO. One-dimensional cuts of the three-dimensional potential energy surfaces (3D-PESs) of these electronic states along the stretch and bend coordinate are calculated. Several avoided crossings and conical intersections are located for bent and linear configurations. The dynamics on the excited electronic states of SNO are very complex, and suggest that multi-step mechanisms s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Comparison of the previous experimental data to the CcCR QFF results lends credence to the assignments of the SNO ν 1 and 2ν 3 modes in the Ar-matrix which are different from the theoretical assignments of Yazidi and coworkers. 14 The intensities computed here also show that the ν 2 bend was not observed in these experiments due to its very low intensity. Additionally, the CcCR VPT2 frequencies for both SNO and OSN compare to the condensed-phase data expectedly giving reason to believe that the CcCR frequencies should also be within 5-15 cm −1 of gas phase experiment as has been noted in the previous benchmarks with the same methodology.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Comparison of the previous experimental data to the CcCR QFF results lends credence to the assignments of the SNO ν 1 and 2ν 3 modes in the Ar-matrix which are different from the theoretical assignments of Yazidi and coworkers. 14 The intensities computed here also show that the ν 2 bend was not observed in these experiments due to its very low intensity. Additionally, the CcCR VPT2 frequencies for both SNO and OSN compare to the condensed-phase data expectedly giving reason to believe that the CcCR frequencies should also be within 5-15 cm −1 of gas phase experiment as has been noted in the previous benchmarks with the same methodology.…”
Section: Discussionmentioning
confidence: 63%
“…There is no doubt that significant mixing and Fermi resonances are taking place for these two modes, but previous experiment 4,5 has assigned the lower frequency mode to ν 1 and the higher frequency mode to 2ν 3 as is given in Table II. Theoretical work by Yazidi and coworkers 14 has inverted that assignment with the admission that significant mixing is taking place. The established CcCR VPT2 methodology utilized here approaches the problem differently than the variational results from Yazidi and coworkers.…”
Section: A Snomentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, we showed that the decomposition of a-oxo azides not only produces the corresponding nitrenes,but their further fragmentation offers unique access to some fundamentally important small molecules like cyclo-N 2 CO [13] and OPN. [14] Particularly,t he generation of O 2 SN, [15] an analogue of SO 3 ,from the flash vacuum pyrolysis (FVP) of CF 3 S(O) 2 N 3 by fragmentation of the weak F 3 C d+ À S d+ bond in CF 3 S(O) 2 N inspired us to investigate the decomposition of the closely related CF 3 S(O)N 3 .Since the F 3 C d+ ÀS d+ bond in CF 3 S(O)N is also expected to be weak because of adominant contribution of the oxathiazyne resonance structure (Scheme 1), its fragmentation would provide access to triatomic OSN, [16] afundamentally important species in sulfur-nitrogen chemistry. [17] According to the recent ab initio calculations, [18] OSN is lower in energy than SNO by about 3kcal mol À1 .Experimentally,SNO has been identified by IR spectroscopy during the l = 121.6 nm photolysis of HNSO [19] and the reaction between sulfur atoms with NO in solid noble-gas matrices.…”
mentioning
confidence: 99%
“…16,17,19,20 Some of these studies were done in support of the matrix isolation experiments. 16,17 Recent work from Yazidi et al 20 and Trabelsi et al 19 also explored the electronic structure of the neutral radicals at a much higher level of theory than previously done (MRCI in Ref. 20 and CCSD(T) with an extrapolation to the complete basis set limit in Ref.…”
Section: Introductionmentioning
confidence: 99%